PENGEMBANGAN POLA DASAR SISTEM DRESSMAKING PADA POSTUR TUBUH PENDEK KURUS - sri wahyunda paputungan; J. CH. Tambahani; Helena V. Opit (Pendidikan Teknik Mesin, 2022)
ABSTRACT archetype Dressmaking is a construction archetype originating from Japan (Dressnaker Jogakuin) specially made for tall skinny body shapes. This allows the dressmaking to be inappropriate if used on other body shapes. The purpose of this study was to develop and describe dressmaking in short skinny women. The type of research is R&D (research & development) using the development model by Sugiyono (2019). The object of this study was tested on women with short stature with a height of 148 cm, and a weight of 42 kg. The data collection technique used is descriptive statistics. The results show that the basic pattern of the Dressmaking has several weaknesses in women of short, thin stature. The results showed that (fitting 1) with a percentage of 75% (body) and 78% (arm), (fitting 2) with an overall percentage of 89%. From the research results, the improvement and development of the basic pattern of the Dressmaking can be adjusted for women of short stature. The results of data analysis on (fitting 3) with a percentage of 97%. Keywords: Development, Dressmaking Pattern, Short Skinny